Stair climbing-descending exercise following meals improves 24-hour glucose excursions in people with type 2 diabetes - Hiroto Honda; Makoto Igaki; Motoaki Komatsu; Shin-ichiro Tanaka; Tetsuo Takaishi; Tatsuya Hayashi (Japanese Society of Physical Fitness and Sports Medicine, 2021)
We aimed at evaluating the effect of short-duration stair climbing-descending exercise (ST-EX) on 24-hour blood glucose (BG) response in people with type 2 diabetes (T2D). Seven men (age, 70.1 ± 1.3 years) with uncomplicated T2D consumed three meals per day according to a meal plan for patients with diabetes. Participants completed one session of ST-EX 60 and 120 min after each meal on the first day (ST-EX day), and did not perform ST-EX on the following day (REST day). Each ST-EX session comprised two 3-min bouts of brisk climbing to the second floor, followed by walking down to the first floor. The BG levels on the experimental days were recorded using a continuous glucose monitoring device. The mean BG level and the area under the curve for BG in the 24-hour period on the ST-EX day were significantly lower than those in the same period on the REST day (both p < 0.05). The duration of hyperglycemia (BG > 10 mmol/L) on the ST-EX day was significantly shorter than that on the REST day (p < 0.05). Repeated 3-min ST-EX after each meal might be an effective strategy to improve 24-hour glucose excursions in people with T2D.